DETERMINANTS OF QUALITY EDUCATION: Discipline, Leadership, and Motivation - Solahudin, Muhammad (AKADEMIK: Jurnal Mahasiswa Humanis, 2022)
The importance of understanding the main factors in building the quality of education. Admittedly or not, quality education is born from many roles and contributions, including school management, teachers, and other parties. Quality education is built on good discipline, initiated by reformist leadership, and supported by education practitioners who have a passion for progress and development. This study was conducted to examine the determinants of quality education, namely the provisions of discipline, the leadership role of school principals and teacher motivation. The proof of the research is done through quantitative techniques and statistical regression analysis. The object of research is the Al-Amanah Al-Gontory educational institution, South Tangerang. While the research unit is the teacher, totaling 115 people. The data was collected through questionnaires, then the research data was processed and analyzed using the SPSS application, including validity, reliability, regression testing, and determination tests. The results of the study explain that quality education is built by many factors, including disciplinary rules that form a regular and measurable personality. Maximum leadership role, thus encouraging all teachers to be able to work with full responsibility and quality. Then work motivation, namely feelings or self-motivation to be able to make a real contribution to school progress. This explanation, confirmed by the results of the regression test, either partially or simultaneously, that discipline, leadership, and motivation are very influential and contribute to improving the quality of education.